The perception of active listening practice on social networks - Pina, L. S.; Loureiro, S. M. C.; Rita, P.; Sarmento, E. M.; Bilro, R. G.; Guerreiro, J. (Global Marketing Conference, 2018)
The evolution of the internet led to a shift in the business operations environment, giving rise to a plethora of challenges and opportunities for companies. Social networks have become attractive to companies due to their interactive nature, not only facilitating conversations with consumers, but also increasing the possibility of enhancing the online consumer brand engagement. Additionally, social networks and online brand communities increased consumers’ possibility of developing an active role in companies’ decision-making process, through the creation of user generated content, together with the opinion sharing and directly information exchange with brands and other internet users. The main objective of this research is to ascertain whether the active listening practice can contribute, in some way, to the improvement of the relationship maintained between consumers and brands. The current study suggests the adaptation of the active listening practice on the online field, as an attempt to enhance the communication strategies held by brands. Hence, this research seeks to demonstrate that this practice can improve the consumer-brand relationship through the development of two qualitative studies, as main approach, where the findings extracted in the first study will be used as inputs to the second one.